Dexamethasone nanomedicines with optimized drug release kinetics tailored for treatment of site-specific rheumatic musculoskeletal diseases - Libánská, Alena; Randárová, Eva; Rubanová, Daniela; Skoroplyas, Svitlana; Bryja, Josef; Kubala, Lukáš; Konefal, Rafał; Navrátilová, Adéla; Cerezo, Lucie A; Šenolt, Ladislav; Etrych, Tomáš (International journal of pharmaceutics, 2024)
The application of polymer-based drug delivery systems is advantageous for improved pharmacokinetics, controlled drug release, and decreased side effects of therapeutics for inflammatory disease. Herein, we describe the synthesis and characterization of linear N-(2-hydroxypropyl)methacrylamide-based polymer conjugates designed for controlled release of the anti-inflammatory drug dexamethasone through pH-sensitive bonds. The tailored release rates were achieved by modifying DEX with four oxo-acids introducing reactive oxo groups to the DEX derivatives. Refinement of reaction conditions yielded four well-defined polymer conjugates with varied release profiles which were more pronounced at the lower pH in cell lysosomes. In vitro evaluations in murine peritoneal macrophages, human synovial fibroblasts, and human peripheral blood mononuclear cells demonstrated that neither drug derivatization nor polymer conjugation affected cytotoxicity or anti-inflammatory properties. Subsequent in vivo tests using a murine arthritis model validated the superior anti-inflammatory efficacy of the prepared DEX-bearing conjugates with lower release rates. These nanomedicines showed much higher therapeutic activity compared to the faster release systems or DEX itself.
Keywords: dexamethason; nanomedicína; Humans; antiflogistika; revmatické nemoci; Drug Carriers; Nanomedicine; doxorubicin; Leukocytes, Mononuclear; Doxorubicin; lidé; zvířata; myši; Drug Liberation; uvolňování léčiv; Mice; polymery; Rheumatic Diseases; Polymers; Dexamethasone; nosiče léků; leukocyty mononukleární; Anti-Inflammatory Agents; Animals